Aspartate aminotransferase to alanine aminotransferase ratio is associated with frailty and mortality in older patients with heart failure - Daichi Maeda (Nature Portfolio, 2021)
Abstract Frailty is a common comorbidity associated with adverse events in patients with heart failure, and early recognition is key to improving its management. We hypothesized that the AST to ALT ratio (AAR) could be a marker of frailty in patients with heart failure. Data from the FRAGILE-HF study were analyzed. A total of 1327 patients aged ≥ 65 years hospitalized with heart failure were categorized into three groups based on their AAR at discharge: low AAR (AAR < 1.16, n = 434); middle AAR (1.16 ≤ AAR < 1.70, n = 487); high AAR (AAR ≥ 1.70, n = 406). The primary endpoint was one-year mortality. The association between AAR and physical function was also assessed. High AAR was associated with lower short physical performance battery and shorter 6-min walk distance, and these associations were independent of age and sex. Logistic regression analysis revealed that high AAR was an independent marker of physical frailty after adjustment for age, sex and body mass index. During follow-up, all-cause death occurred in 161 patients. After adjusting for confounding factors, high AAR was associated with all-cause death (low AAR vs. high AAR, hazard ratio: 1.57, 95% confidence interval, 1.02–2.42; P = 0.040). In conclusion, AAR is a marker of frailty and prognostic for all-cause mortality in older patients with heart failure.